Role of Primary Health Care in the 21st Century - VS Ariyaratne (College of Community Physicians of Sri Lanka, 2012)
Journal of the College of Community Physicians of Sri Lanka Volume 16, No. 02, December 2011 2-14 DOI: http://dx.doi.org/10.4038/jccpsl.v16i2.4575